(untitled) (Contemporary Journal of Social Science Review, 2025)
This research paper critically examines the scholarly contributions of two pioneering Western orientalists—Ignaz Goldziher (1850–1921) and Reynold A. Nicholson (1868–1945)—and their influence on the academic study of Islam in the twentieth century. The study explores how both scholars, despite their Western academic frameworks, significantly advanced global understanding of Islamic history, theology, Sufism, and literature. Goldziher, often considered a founding figure in the modern study of Islam, brought rigorous philological and historical methodologies to the analysis of ḥadīth literature and Islamic jurisprudence. His critical approach opened new avenues for examining the development of Islamic traditions beyond traditional narratives. Nicholson, on the other hand, is recognized for his seminal translations and interpretations of classical Sufi texts, particularly his work on Jalāl al-Dīn Rūmī and Kashf al-Maḥjūb. He played a crucial role in introducing Sufi metaphysics and Persian literature to the Western academic world. The paper also addresses the critiques of both scholars from Muslim academics, especially regarding issues of interpretative bias, cultural misrepresentation, and methodological limitations. By comparing their approaches, the research assesses the balance between scholarly contribution and orientalist subjectivity. Furthermore, the paper evaluates the enduring legacy of Goldziher and Nicholson in contemporary Islamic studies, highlighting how their works still inform curriculum, discourse, and debates in Islamic scholarship today. This study ultimately seeks to present a nuanced and critical perspective on how Western scholars have helped shape the field of Islamic studies, while also examining the tensions and dialogues between East and West in this academic domain.